Blockchain applications in health insurance: a review of applications, challenges, and prospects - Chen, Yisong; Zhao, Chuqing; Gao, Yifan (Frontiers in Blockchain, 2025)
IntroductionThis systematic review comprehensively examines the application of blockchain in health insurance, highlighting the current state of research, inherent challenges, and future trends. Blockchains have demonstrated excellent potential in health insurance, especially in fraud prevention, claims processing, and data security. Moreover, this study also aims to identify several critical challenges that hinder their broader adoption and effectiveness, including data heterogeneity, individual task requirements, scalability and regulatory alignment.MethodsSystem ReviewResults and DiscussionThrough comprehensive analysis, this study discusses some actionable solutions and strategies. Conclusively, this review underscores blockchain’s transformative impact on building a secure, efficient, and patient-centric health insurance system.